Comparison of the Analytical Hierarchy Process Method and the Simple Additive Weighting Method in the Selection of the Best Fiction Books in the 1990s - Armansyah, Armansyah; Siregar, Yustria Handika; Irawan, Muhammad Dedi; Armayani, Cici; Habib, Maulana (International Conference on Sciences Development and Technology, 2021)
A fiction book is a story book written based on the imagination of an author, the stories contained in fiction books are stories that entertain readers. In the era of the 1990s fiction books were books that had a lot of interest among the people at that time. This study aims to determine the feasibility of fiction books to be categorized as the best fiction books. The problem of this research is in the assessment process which only judges from reader reviews, it is not effective for making a selection of fiction books, so to solve this problem, a decision support system will be implemented using the Analytical Hierarchy Process (AHP) and Simple Additive Weighting (SAW) methods. system with multi-attribute decision making. In this study, the criteria for copies with a value of 35% will be used as a benchmark for assessing the selection of fiction books. Then the results issued by the system using the AHP method will show the transparency of the assessment with each value and have a certain weight according to the priority and the final results of ranking the two AHP and SAW methods will produce the same alternative with the highest alternative value which will be recommended as a fiction book that has the right to be the best fiction book in the 1990s era.